1999
DOI: 10.1007/s004170050283
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic proof of the toxicity of mitomycin C on the ciliary body in relation to different application methods

Abstract: Severe morphologic alterations were seen at the electron-microscopic level after application of MMC 0.2 mg/ml with a collagen shield and with a soft contact lens. They were mildest with lyophilisate and absent in the BSS controls. A new administration device is needed if trabeculectomy is to be performed successfully using MMC in human glaucomatous eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
7

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 26 publications
0
21
0
7
Order By: Relevance
“…Schraermeyer et al [12] examined the application of 0.2 mg/ml MMC to the episclera for 5 min via three delivery routes -collagen shield, soft contact lens, and lyophilisate -to minimize adverse effects, and they detected severe morphologic deformities in tissues regardless of the delivery route chosen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schraermeyer et al [12] examined the application of 0.2 mg/ml MMC to the episclera for 5 min via three delivery routes -collagen shield, soft contact lens, and lyophilisate -to minimize adverse effects, and they detected severe morphologic deformities in tissues regardless of the delivery route chosen.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that episcleral MMC damages the ciliary body [10][11][12] . Studies have been conducted to determine the minimum effective concentration and duration of MMC use in trabeculectomy to prevent or lessen these complications; however, there is no con-sensus of results.…”
Section: Introductionmentioning
confidence: 99%
“…Hypotony occurs with antimetabolite use due to overfiltration at the bleb site or underproduction of aqueous by the effect of antimetabolites on the ciliary body, or both. 98,99 It has been suggested that a thin sclera predisposes an eye to postoperative hypotony. [100][101][102] The high prevalence of myopia (and hence thinner sclera) in the Chinese population may be relevant in this respect.…”
Section: Characteristics Of East Asian Eyesmentioning
confidence: 99%
“…This effect was stronger if cyclohexamide was also added. used agents 5-¯uorouracil (Franks and Hitchings, 1991;Ticho and Ophir, 1993) and mitomycin-C (Derick et al, 1991;Singh et al, 1995;Matsuda et al, 1996;Schraermeyer et al, 1999) show the need for new supportive drugs with less side effects.…”
Section: Cd95l Induced Apoptosis Is Mediated Via Caspase 3 (Cpp32)mentioning
confidence: 99%
“…Success rates have been enhanced with the introduction of adjuvant drug treatment, but failures still occur, especially in cases of complicated glaucoma. These failures and possible toxic side effects of the most frequently used drugs 5-¯uorouracil (Franks and Hitchings, 1991;Ticho and Ophir, 1993) and mitomycin-C (Derick et al, 1991;Singh et al, 1995;Matsuda et al, 1996;Schraermeyer et al, 1999) in glaucomatous ®ltering procedures call for alternative approaches to control ®broblast proliferation. Over the past decade researchers in the ®eld of cancer treatment have focussed on apoptosis induction to eliminate fast growing tissues.…”
Section: Introductionmentioning
confidence: 99%